Molecular phylogeny and morphology reveal a new species of Dichostereum (Russulales) from Guangxi Autonomous Region, southern China - Hao, Hong-Wei; Zeng, Guang-Yu; Dai, Yu-Cheng (Phytotaxa, 2026)
Based on morphological characteristics and molecular phylogenetic analysis of ITS+nLSU sequences, this study reports a new wood inhabiting species in Russulales, Dichostereum olivaceoluteum. It was discovered in subtropical forest of Guangxi Autonomous Region, southern China. The new species is characterized by perennial, resupinate basidiomata with olivaceous buff hymenophore, difficult to separate from substrate; microscopically it has a dimitic hyphal system with clamp connections on generative hyphae, and thick-walled, globose, ornamented basidiospores measuring 6.2–7.4 × 5.5–7.0 μm.